Assessment of Risk Factors for Fractures in Patients with Type 2 Diabetes over 60 Years Old: A Cross-Sectional Study from Northeast China - Yan Guo; Yingfang Wang; Feng Chen; Jiabei Wang; Difei Wang (Journal of Diabetes Research)
Aims. Previous evidence has demonstrated an increased fracture risk among the population with type 2 diabetes mellitus (T2DM). This study investigated the prevalence of bone fractures in elderly subjects (with and without type 2 diabetes) and identified any fracture risk factors, especially the risk factors for common known fractures in particular diabetic populations. Methods. This cross-sectional study was conducted with community-dwelling people over 60 years old in nine communities from the city of Shenyang, which is the capital of Northeast China’s Liaoning Province. A total of 3430 elderly adults (2201 females, mean±standard deviation age 68.16±6.1 years; 1229 males, 69.16±6.7 years) were included. Our study measured the heel bone mineral density (BMD) and used the timed “up and go” (TUG) test and other indicators. In addition, we performed logistic regression analysis to explore the risk factors for fractures in the general population and the diabetic population and to analyze the differences. Results. The results revealed that a total of 201 elderly persons (5.8%), with an average age of 70.05±6.54 years, suffered from a history of fragility fractures, which affected more females (74.6%) than males (p=0.001). The prevalence of fractures in the T2DM population was 7.3%, which was much higher than the 5.2% in non-T2DM population (p<0.05). In the non-T2DM population, the BMD was lower and the TUG time was longer in the fracture group than in the nonfracture group (p<0.001). However, in the T2DM population, the BMD and TUG values were similar between the fracture group and the nonfracture group (p>0.05). Logistic regression analysis showed that the female sex (OR 1.835), TUG time>10.2 s (OR 1.602), and T‐score≤−2.5 (OR 1.750) were independent risk factors for fragility fractures in the non-T2DM population, but they were not risk factors in the T2DM population. Conclusions. This study found that low BMD and slow TUG time were independent risk factors for fractures in non-T2DM patients, while no associations were found in the T2DM population. Patients with T2DM have a higher risk for fractures even when they have sufficient BMD and a short TUG time. TUG and BMD underestimated the risk for fractures in the T2DM population.